2021
DOI: 10.3390/rs13173517
|View full text |Cite
|
Sign up to set email alerts
|

Development and Testing of a UAV-Based Multi-Sensor System for Plant Phenotyping and Precision Agriculture

Abstract: Unmanned aerial vehicles have been used widely in plant phenotyping and precision agriculture. Several critical challenges remain, however, such as the lack of cross-platform data acquisition software system, sensor calibration protocols, and data processing methods. This paper developed an unmanned aerial system that integrates three cameras (RGB, multispectral, and thermal) and a LiDAR sensor. Data acquisition software supporting data recording and visualization was implemented to run on the Robot Operating … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 55 publications
0
10
0
Order By: Relevance
“…A model incorporating both plant height and canopy cover was created to predict yield. Xu et al (2021) developed an unmanned aerial system integrating three types of imaging sensors (RGB, multispectral, and thermal) as well as a LiDAR sensor to monitor cotton morphological traits (canopy height, canopy cover, and canopy volume), canopy vegetation index, and canopy temperature. Validation tests in a cotton field showed the multisensor aerial system to be a useful tool for cotton breeding and precision management.…”
Section: Plant Growthmentioning
confidence: 99%
“…A model incorporating both plant height and canopy cover was created to predict yield. Xu et al (2021) developed an unmanned aerial system integrating three types of imaging sensors (RGB, multispectral, and thermal) as well as a LiDAR sensor to monitor cotton morphological traits (canopy height, canopy cover, and canopy volume), canopy vegetation index, and canopy temperature. Validation tests in a cotton field showed the multisensor aerial system to be a useful tool for cotton breeding and precision management.…”
Section: Plant Growthmentioning
confidence: 99%
“…Using machine vision, picture segmentation, and big data processing technologies to reliably gather and analyze crucial plant traits is an important technical means for the development of contemporary agriculture, with significant guiding value for crop management and genetic breeding (Granier and Vile, 2014 ; Li et al, 2021 ). Scholars have conducted field studies on the morphological indicators of dicotyledonous crops, including stem height (Paproki et al, 2012 ), plant height (Sun et al, 2017 ), leaf width (Paproki et al, 2012 ), leaf length (Paproki et al, 2012 ), number of leaves (Dobrescu et al, 2020 ), canopy coverage (Kirchgessner et al, 2016 ; Borra-Serrano et al, 2020 ; Wan et al, 2021 ; Xu et al, 2021 ), canopy height (Kirchgessner et al, 2016 ; Borra-Serrano et al, 2020 ), canopy roughness (Herrero-Huerta et al, 2020 ), and flowers (Xu et al, 2017 ; Jiang et al, 2020 ).…”
Section: Research Status Of High-throughput Phenotypic Information Of...mentioning
confidence: 99%
“…Moreover, similar research has been conducted on cotton, rape, and other crops. Xu et al ( 2021 ) created a UAV system with three cameras (RGB, multispectral, and thermal) and a lidar sensor to identify cotton canopy coverage and canopy height, with an average relative error of only 6.6%. The approach of collecting crop morphological data from RGB images is quite accurate.…”
Section: Research Status Of High-throughput Phenotypic Information Of...mentioning
confidence: 99%
See 1 more Smart Citation
“…Infrared thermography is increasingly used in non-destructive condition monitoring services as a less labor-intensive and non-contact technique to assess vegetation stress by leaf canopy temperature [ 12 , 13 , 14 , 15 ]. Canopy temperature has been widely used to detect stress because the closing of the stomas on the leaves is controlled to retain water during the stress, resulting in changes in stomatal conductance, transpiration, and leaf temperature [ 16 , 17 , 18 , 19 , 20 , 21 ]. Some research found that the canopy temperature between the stressed vegetation and healthy vegetation was different [ 22 , 23 , 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%